The Hybrid Moorish Style Characteristic in Malaysia: Bandar Istana Jugra - Lee, Nur Irdina; Farah Afiqah; Shukri, Sharyzee Mohmad (MAJ - Malaysia Architectural Journal, 2020)
Over the years, many architectural styles can be seen throughout Malaysia in history and in present times. The Moorish style is one of them. However, with change come a combination of different styles which created the Hybrid Moorish style and Istana Bandar Jugra is one such historic building that possesses this style and is still standing. Istana Bandar Jugra which is located in Banting, was one of the royal palace of Selangor for the Sultan of its times. This research aims to study about the characteristics and its unique features of the Hybrid Moorish style that is found in history and in Malaysia now and how Istana Bandar possess such traits. The method of this research is focusing is done through in-depth literature review, site observations and interview, and comparison of other historic buildings throughout the world, we learnt of the characteristics that's unique to this style that is seen throughout. Through our findings in the case study, we discovered that Istana Bandar Jugra possesses such traits and can be seen throughout the building, and to preserve it, conservation strategies are applied. By this research, we revealed that Moorish architecture can be seen not only in its own architecture style but as well as one hybrid style which by example, Istana Bandar Jugra too, showcase its unique features.